Medicine Meets Virtual Reality 15 in vivo, in vitro, in silico: Designing the Next in Medicine - Westwood, James D (IOS Press, 2013)
Many different reasons, such as disease, accident, crime, and war, may cause large cranial defects. A technique for cranial implant design using patient CT data has been developed by Dujovny and Evenhouse et al., which builds patient-specific implants.[1] This method generates a computer polygonal model of the skull and defect from the patient’s CT data, and a physical model of the skull with defect is built after the model is exported to a stereolithography machine. Using this model as a template, the implant is designed and fabricated using wax to sculpt the missing tissue. A mold is made to cast the implant. Although this method results in patient specific implants with near perfect fit, it is expansive and timeconsuming.